Price Transmission from International to Domestic Markets - Greb, Friederike; Jamora, Nelissa; Mengel, Carolin; Von Cramon-Taubadel, Stephan; Wurriehausen, Nadine (World Bank, Washington, DC, 2016)
This study aims to improve our understanding of the extent and speed of the transmission of international cereal prices to local markets in developing countries. We undertake three types of analysis. First, we extract a sample of estimated measures of cereal price transmission (PT) from a comprehensive literature sample of published papers and studies. Second, we use the FAO’s GIEWS dataset to estimate our own sample of measures of cereal PT. In a subsequent meta-regression analysis we measure how much of the variation in each of the resulting samples of PT estimates (the literature sample and the GIEWS sample) can be explained by factors that might be expected to influence the strength of PT such as whether the country in question is landlocked. Third, we present the results of simple, non-parametric analysis of price transmission using the GIEWS data. This analysis measures the share of periods in which domestic and international prices have jointly increased or decreased.